Kekuatan Tarik Baja St 37 pada Proses Las Oksi - Asetilen - Akhmad Syarief (Universitas Lambung Mangkurat, 2004)
Welding is a process of joining metals by pressure when the metal are hot. Welding planning to get a good result is a complicated process. A welding work should be planned about its way, observing the material and its type of welding. The procedure of welding involves: choosing parameter of welding type of being used, type of filling metal, type and also the thickness of metal plat and condensor as mediator and some standartd condition in welding in which the parameters will effect the mechanical characters of welding.An example of welding type is Oxy-Acetyline Welding (OAW). The heat being produced is lower, so this kind of welding is good to weld the thinner stainless steel ( 3 mm). The thicker one needs a longer welding time so that, it is not economic. This kind of welding is good for a thick stainless steel before using electrical welding. This welding is used for a simple construction that is not need strength, example in the fenceof a house or for welding a house hold.This process, uses material of ST-37 steel plate with 3 mm thickness. Weld with 1-2 mm in space between thew both material. Set the barometer up on the acetyline bottle is about 0,5 bar and the pressure on oxyigene bottle is about 2,5 bar, and a weather condensor. Use RBuZn-A, RBuZn-B and RBuZn-D as filling metal. Then do test.